Deontología profesional y su influencia en las competencias administrativas de las secretarias - Gavilanez Campbell, Karen Jamilet (2020)
The present case study is aimed at determining professional deontology and its influence on the administrative competencies of the secretaries of the Administrative Directorate of the Technical University of Babahoyo. The study was carried out through descriptive research, which allowed identifying the characteristics of the variables and how to get to know the principles and rules of ethics that regulate and govern a professional activity. In the same way, it was applied as an instrument to the interview, conducted to 3 officials of the Administrative Directorate of the Technical University of Babahoyo to know how often the deontological codes are applied in the workplace. On the other hand, at present, the professions have made their own codes and, in this sense, can speak of a professional deontology. In the same way these rules are those that can be determined by the department of a company itself and the modifications in an obligation and commitment so it has a coercive projection within the administrative competences, these determine the level of responsibility, participation, leadership in decision-making for the benefit of the entity and it allows reliability among all the officials of said institution.